2016
DOI: 10.1017/s0033291716001902
|View full text |Cite
|
Sign up to set email alerts
|

Impaired glucose tolerance in first-episode drug-naïve patients with schizophrenia: relationships with clinical phenotypes and cognitive deficits

Abstract: IGT occurs with greater frequency in FEDN schizophrenia, and shows association with demographic and anthropometric parameters, as well as with clinical symptoms but minimally with cognitive impairment during the early course of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 79 publications
1
40
0
Order By: Relevance
“…Overall, we identified 31 eligible studies for inclusion in this meta‐analysis (Tables S3 and S4) (Arranz et al, ; Basoglu et al, ; Cai et al, ; Canan et al, ; Chang et al, ; Chen et al, ; Chen et al, ; Dasgupta, Singh, Rout, Saha, & Mandal, ; Enez Darcin, Yalcin Cavus, Dilbaz, Kaya, & Dogan, ; Fernandez‐Egea et al, ; Garcia‐Rizo et al, ; Garcia‐Rizo et al, ; Grover, Nebhinani, Chakrabarti, Avasthi, & Kulhara, ; Kavzoglu & Hariri, ; Keinanen et al, ; Leo et al, ; Misiak et al, ; Nyboe, Vestergaard, Moeller, Lund, & Videbech, ; Petrikis et al, ; Ryan et al, ; Saddichha, Manjunatha, Ameen, & Akhtar, ; Saloojee, Burns, & Motala, ; Sengupta et al, ; Spelman et al, ; Turan, Kesebir, & Suner, ; van Nimwegen et al, ; Venkatasubramanian et al, ; Wani et al, ; Wu et al, ; Yildirim et al, ; Zhang et al, ). Of these studies, one was conducted with patients who had a first episode mania (Turan et al, ), five were conducted with patients who had first episode depression (Canan et al, ; Chang et al, ; Garcia‐Rizo et al, ; Grover et al, ; Leo et al, ) and one was conducted with patients who had first episode mania or depression (Garcia‐Rizo et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, we identified 31 eligible studies for inclusion in this meta‐analysis (Tables S3 and S4) (Arranz et al, ; Basoglu et al, ; Cai et al, ; Canan et al, ; Chang et al, ; Chen et al, ; Chen et al, ; Dasgupta, Singh, Rout, Saha, & Mandal, ; Enez Darcin, Yalcin Cavus, Dilbaz, Kaya, & Dogan, ; Fernandez‐Egea et al, ; Garcia‐Rizo et al, ; Garcia‐Rizo et al, ; Grover, Nebhinani, Chakrabarti, Avasthi, & Kulhara, ; Kavzoglu & Hariri, ; Keinanen et al, ; Leo et al, ; Misiak et al, ; Nyboe, Vestergaard, Moeller, Lund, & Videbech, ; Petrikis et al, ; Ryan et al, ; Saddichha, Manjunatha, Ameen, & Akhtar, ; Saloojee, Burns, & Motala, ; Sengupta et al, ; Spelman et al, ; Turan, Kesebir, & Suner, ; van Nimwegen et al, ; Venkatasubramanian et al, ; Wani et al, ; Wu et al, ; Yildirim et al, ; Zhang et al, ). Of these studies, one was conducted with patients who had a first episode mania (Turan et al, ), five were conducted with patients who had first episode depression (Canan et al, ; Chang et al, ; Garcia‐Rizo et al, ; Grover et al, ; Leo et al, ) and one was conducted with patients who had first episode mania or depression (Garcia‐Rizo et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Of these studies, one was conducted with patients who had a first episode mania (Turan et al, ), five were conducted with patients who had first episode depression (Canan et al, ; Chang et al, ; Garcia‐Rizo et al, ; Grover et al, ; Leo et al, ) and one was conducted with patients who had first episode mania or depression (Garcia‐Rizo et al, ). Twenty‐four were conducted in patients with FEP (Arranz et al, ; Basoglu et al, ; Cai et al, ; Chen, Broqueres‐You, et al, ; Chen, Du, et al, ; Dasgupta et al, ; Enez Darcin et al, ; Fernandez‐Egea et al, ; Kavzoglu & Hariri, ; Keinanen et al, ; Misiak et al, ; Nyboe et al, ; Petrikis et al, ; Ryan et al, ; Saddichha et al, ; Saloojee et al, ; Sengupta et al, ; Spelman et al, ; van Nimwegen et al, ; Venkatasubramanian et al, ; Wani et al, ; Wu et al, ; Yildirim et al, ; Zhang et al, ). Among FEP studies, one study included patients with schizoaffective disorders (n = 4) in their patient group (n = 38) (Sengupta et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Studies have shown that metabolic disturbances, such as impaired glucose tolerance, insulin resistance, and endothelial dysfunction, may exist prior to the development of schizophrenia. [5][6][7] However, whether a dysregulated metabolic state and endothelial dysfunction cause or are a consequence of schizophrenia remains unknown. 5,7,8 Increasing evidence found that use of atypical antipsychotics was associated with an elevated likelihood of glucose dysregulation 9,10 and suggested that changes of molecules linked to insulin resistance may be independent of the effects of atypical antipsychotics among patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] However, whether a dysregulated metabolic state and endothelial dysfunction cause or are a consequence of schizophrenia remains unknown. 5,7,8 Increasing evidence found that use of atypical antipsychotics was associated with an elevated likelihood of glucose dysregulation 9,10 and suggested that changes of molecules linked to insulin resistance may be independent of the effects of atypical antipsychotics among patients with schizophrenia. 8,[11][12][13] The finding of an elevated risk of type 2 diabetes mellitus (T2DM) in the absence of atypical antipsychotics may imply the shared pathophysiology between schizophrenia and T2DM.…”
Section: Introductionmentioning
confidence: 99%